Between East and West. Coinage of the Rhodian poleis in the Archaic and Classical periods - Mielczarek, Mariusz (Acta Archaeologica Lodziensia, 2018)
The island of Rhodes, situated near Asia Minor, was an area in which cultural and economic influences from Asia Minor and the Greek world met in Antiquity. Effects of this situation are visible in the coinages of the Rhodian poleis in the Archaic and Classical periods. Ialysos, Lindos and Kamiros issued coins from the last quarter of the 6th century BC to 408/407 BC, i.e. to the time of founding of the city of Rhodes. The history of the coinage of each city is discussed. Coin iconography and different weight systems used in coin production are related to the prevailing political and economic situation. The trade connections of the three Rhodian poleis with Asia Minor, the Levant and Egypt also had a strong influenced on Rhodian coinage. These trade relations well attested by the location of coin hoards consisting of coins of Ialysos, Lindos and Kamiros. Special attention is given to the electrum coins minted by the Rhodian poleis. A special topic of the discussion is the reasons why electrum coinage was produced.